A distance‐sensitive distributed repulsive sleeping approach for dependable coverage in heterogeneous cellular networks. Issue 11 (12th November 2019) - Tang, Liangrui; He, Yanhua; Zhou, Zhenyu; Ren, Yun; Mumtaz, Shahid; Rodriguez, Jonathan
Abstract: Base station (BS) sleeping technology has become one of the significant technologies in fifth‐generation green communications. However, enormous communication overhead and coverage holes produced by existing sleeping strategies will decline the robustness of the network. To tackle this problem, this paper proposes a distance‐sensitive distributed repulsive sleeping strategy (DSDRSS), based on hard‐core point process (HCPP). First, through information exchanges, presleeping BSs in the same region form a sleeping cluster (SC) whose size is limited by sleeping distance. Second, BSs in the SC perform BS sleeping with a mark method where BSs will be randomly assigned a mark, and BSs with the lowest mark will remain on to ensure the coverage. Third, to characterize the performance of DSDRSS, the analytical expressions of sleeping probability, coverage probability, and average achievable rate for user equipment (UE) under DSDRSS are derived. Finally, the coverage characteristics of UE under DSDRSS are analyzed and compared with those under different sleeping operations. DSDRSS realizes sleeping operations through the cooperation between BSs in an SC, not relying on the feedback links between a small BS and the control center. As a result, DSDRSS can not only enable flexible perception of traffic changes in sleeping area but also complete sleeping with less overhead. The simulation results show that DSDRSS supports more dependable coverage compared with random sleeping strategy and general repulsive sleeping strategy. Abstract : Enormous communication overhead and coverage holes produced by existing sleeping strategies will decline the robustness of the network. To tackle this problem, a distance‐sensitive distributed repulsive sleeping strategy (DSDRSS) is proposed to support dependable coverage for heterogeneous network, based on the hard‐core point process. With the coverage sacrifice of the macro base station user equipment (MUE), DSDRSS could get the optimal coverage for small base station UE; without the coverage sacrifice of MUE, DSDRSS could get the 20% coverage gain.